Heating up the battle: the role of the media in the souring of Malaysia - Indonesia relations / Ruhanas Harun - Harun, Ruhanas (Centre for Media and Information Warfare Studies, 2009)
The media, especially the press and television have become powerful instruments in shaping public opinion on domestic and international issues. The current disharmony in Malaysia-Indonesia bilateral relations is an example of the importance of mass media in influencing the perception of people about one another. For most people in the region, the mass media are the major sources of information about current events, people and politics. The advent of new forms of communications has made it easier for peoples to get in contact with one another and to disseminate information and an amazing speed, even if the information is not always accurate. Besides the current spat in Malaysia-Indonesia bilateral relations, the Malaysia-Singapore conflict in 1998 over contentious issues, fought mainly in the media of both countries also highlights the important role of the media in international diplomacy.